2020
DOI: 10.1021/acscatal.9b03178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Active Phase in K-Promoted MoS2 Catalysts for Methanethiol Synthesis

Abstract: K-promoted MoS 2 is an active catalyst for the synthesis of CH 3 SH, a valuable chemical intermediate, from synthesis gas (CO/H 2 ) and H 2 S. The promotion of MoS 2 by K increases the CO conversion rate and the CH 3 SH selectivity and is usually linked to the stabilization of the 1T-MoS 2 polymorph as compared to the 2H-MoS 2 in K-free samples. Sulfided catalysts were characterized using TEM, XPS, and EXAFS. TEM showed that MoS 2 particles became larger and more stacked when the K/Mo ratio increased above uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 50 publications
0
51
1
Order By: Relevance
“…To sum up, as far as the synthesis of CH3SH by CS2 hydrogenation is concerned, we have concluded that the main active site of the catalysts is the weak Lewis acid-base site, and the strong acidic site and strong basic site are not conducive to the formation of CH3SH. In addition, it is generally believed that the active phase for the synthesis of CH3SH over K-promoted MoS2-based catalysts is the K-Mo-S phase [8,10,11,16], but in this paper, we did not pre-sulfurization the catalyst before the reaction, so it can be considered that apart from the K-Mo-S phase, the K-Mo-O phase may also be the main active phase.…”
Section: Proposed Mechanism On the Acid-base Sitementioning
confidence: 99%
See 2 more Smart Citations
“…To sum up, as far as the synthesis of CH3SH by CS2 hydrogenation is concerned, we have concluded that the main active site of the catalysts is the weak Lewis acid-base site, and the strong acidic site and strong basic site are not conducive to the formation of CH3SH. In addition, it is generally believed that the active phase for the synthesis of CH3SH over K-promoted MoS2-based catalysts is the K-Mo-S phase [8,10,11,16], but in this paper, we did not pre-sulfurization the catalyst before the reaction, so it can be considered that apart from the K-Mo-S phase, the K-Mo-O phase may also be the main active phase.…”
Section: Proposed Mechanism On the Acid-base Sitementioning
confidence: 99%
“…More and more researchers are mainly focused on finding a more economical and environmentally friendly synthesis routes in recent years. Among them, the catalytic synthesis of CH 3 SH from sulfur-containing synthesis gas has aroused great interest among researchers [7][8][9][10][11][12][13][14], but the conversion and yield of CH 3 SH are relatively low, which does not meet the requirements of large-scale industrialization. CS 2 is relatively surplus and the price is low at present, and the one-step synthesis of CH 3 SH by CS 2 hydrogenation has the advantages of low reaction temperature (260~280 • C) and fewer three wastes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sam ples showed strong and sharp Raman active modes from TiO x species. [39,40] In addition, a large luminescence background at 1000-2000 cm −1 was detected, which was generated from the excitation in the intrabands in TiO x , and implied the existence of structural disorder defects in TiO x . [41] Furthermore, after Au NPs deposition, the luminescence background has been remarkably quenched, which revealed effective charge transfer between Au NPs and TiO x , and thus the optical energy can be efficiently converted into electricity, thus quenched the lumi nescence.…”
Section: Photonic-plasmonic Resonatorsmentioning
confidence: 99%
“…Considerable attention has been devoted to two-dimensional (2D) materials as promising functional materials, in particular to transition metal dichalcogenides (TMDCs) [ 1 , 2 , 3 , 4 ], due to rapid advances in synthesis, transfer, spectroscopic detection, and manipulation. Since 2D TMDCs have unique physicochemical properties such as high mobility, large surface area, and significant catalytic activities, they can be effectively used for efficient light harvesting, sensitive photo-detection, and catalytic conversion systems [ 5 , 6 , 7 , 8 ]. Among 2D TMDCs, particularly, tungsten disulfide (WS 2 ), with direct optical band gaps of 1.35 and 2.05 eV for bulk and monolayer structure, is of great interest due to its particular semiconducting behavior, intrinsic electrical conductivity, and electrocatalytic property when the number of layers is lower [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%